1990
DOI: 10.1161/01.cir.81.5.1622
|View full text |Cite
|
Sign up to set email alerts
|

Thallium 201 kinetics in stunned myocardium characterized by severe postischemic systolic dysfunction.

Abstract: The hypothesis tested in this study was that despite the presence of severe postischemic myocardial dysfunction ("stunning")

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
2

Year Published

1991
1991
2006
2006

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(10 citation statements)
references
References 67 publications
0
7
1
2
Order By: Relevance
“…An experimental study demonstrated that thallium-201 extraction was unaltered in the stunned myocardium. 9 However, in the present case persistent thallium-201 perfusion defects were observed on the images obtained soon after the onset of myocardial infarction. This finding indicates that acute ischemic insult can result in severe metabolic disturbance.…”
Section: Discussioncontrasting
confidence: 51%
“…An experimental study demonstrated that thallium-201 extraction was unaltered in the stunned myocardium. 9 However, in the present case persistent thallium-201 perfusion defects were observed on the images obtained soon after the onset of myocardial infarction. This finding indicates that acute ischemic insult can result in severe metabolic disturbance.…”
Section: Discussioncontrasting
confidence: 51%
“…The computer automatically calculated wall thickness in 32 chords along the LV circumference ( Figure 3C). 15 The average thickening along the 32 chords represented global LV thickening. Average thickening within the operator defined regions of reduced thickening during ischemia were also automatically calculated.…”
Section: Analysis Of Echocardiographic Imagesmentioning
confidence: 99%
“…The initial uptake of this tracer is dependent on flow but if flow is relatively uniform, the distribution of the tracer 20 to 30 min after injection is related to viability (31). ' ' IT1 has been the favored tracer of myocardial viability in nuclear medicine for over a decade, and its distribution characteristics have been extensively studied (32)(33)(34)(35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%